Assessing the Efficacy of Differentiated Instruction for Neurodiverse Students within Inclusive Settings - Robert, Bukayo; Jordan, Inaki (Journal of Current Research In Multidisciplinary, 2026)
This research assesses the efficacy of Differentiated Instruction (DI) as a pedagogical framework for supporting neurodiverse learners within inclusive general education settings. As classrooms become increasingly diverse, the traditional "one-size-fits-all" approach often fails to meet the unique cognitive and socio-emotional needs of students with ADHD, autism, and dyslexia. Employing a mixed-methods case study design, this research gathered data through systematic classroom observations, semi-structured teacher interviews, and student progress reports over a twelve-week period. The findings indicate that the implementation of tiered assignments and flexible learning pathways significantly enhances student engagement and academic performance. Moreover, the study reveals that a positive inclusive classroom culture is a critical prerequisite for the success of these instructional strategies. However, significant challenges remain, particularly regarding teacher workload and the need for systemic administrative support. The study concludes that while Differentiated Instruction is a powerful tool for promoting educational equity, its long-term sustainability requires dedicated professional development and collaborative teaching models. These results provide an evidentiary basis for policymakers and educators to prioritize neurodiversity-informed pedagogy in mainstream curricula.